Peningkatan Kualitas Produk Roti Manis pada PT Indoroti Prima Cemerlang Jember Berdasarkan Metode Statistical Process Control (SPC) dan Failure Mode and Effect Analysis (FMEA) - Elisa Mardya Ratri; Eka Bambang G; Marmono Singgih (e-Journal Ekonomi Bisnis dan Akuntansi, 2018)
This study aims to control the quality of sweet bread products at PT Indoroti Prima Cemerlang Jember by analyzing the total amount of bread produced and the amount of bread that is damaged over a period of time using Statistical Process Control (SPC) and Failure Modes and Effect Analysis ( FMEA).. Selection of sweet bread that will be studied is based on the proven data of bread production on Januari 2017 which show that the most damaged product were found in sweet bread variant, so it needs to get more attention from the company in priority improvement. Based on the p chart, the damage of sweet breads is within control limits. It is indicated by the whole point that are within UCL dan LCL. The UCL line is 0,0930, LCL line is 0,0238, and p (midline) is 0,0085. The types of damage which happened to the sweet breads are dents, filthy, leak, defated, and truncated. The damaged can be caused by three factors such as man, machine, and method. Based on FMEA (Failure Mode and Effect Analysis) Method, it shows that the priority improvement for production and packing process are different. Improvement in production process prioritized on man factor, while improvement in packing process prioritized on machine factor. Keywords: Failure Mode and Effect Analysis (FMEA), Quality Control, Statistical Process Control (SPC)